Investigation of aged hot-mix asphalt pavement moduli. - Thomas, Jeremiah (Kansas State University, 2011)
Over the lifetime of an asphalt concrete (AC) pavement, the roadway requires periodic resurfacing and rehabilitation to provide acceptable performance. The most popular resurfacing method is an asphalt overlay over the existing roadway. In the design of asphalt overlays, the thickness is related to the structural capacity of the existing pavement. As the layers are overlaid, their structural characteristics change due to aging of asphalt. However, currently there is no method to determine the effect of aging on the structural capacity of an existing pavement. This study examined structural characteristics of six test roadways in Kansas using three different test methods: Falling Weight Deflectometer (FWD), Portable Seismic Property Analyzer (PSPA), and Indirect Tensile (IDT) test. The results were analyzed to determine how the modulus of an AC pavement layer changes over time. The results indicate that as the AC pavement ages, its modulus decreases due to pavement deterioration, especially stripping. Two test roadways that showed little signs of stripping had a minimal reduction or even an increase in AC moduli. Thus, the stripping issue needs to be addressed to ensure longevity of AC pavements. While the correlation between test methods studied was mostly consistent for each roadway, no universal correlation was found. The structural coefficient of each AC layer was determined based on the resilient modulus of the layer. It was found the structural layer coefficients do not typically decrease with age at the same rate, and the rate of decrease is a function of the distresses observed.
Keywords: Asphalt; Pavement; Modulus; Aged; Overlay; Structural; Civil Engineering (0543); Engineering (0537); Transportation (0709)